Relationship between Perceived Organizational Justice and Quality of Working Life Mediated by Job Involvement among the Iranian Red Crescent Society Staff - Sheikhi Ghalehsardi, Rahman; Heidari, Alireza; Asgari, Parviz; Eftekhar Saadi, Zahra (Advances in Nursing & Midwifery, 2023)
Introduction: Organizations attempt to retain and grow their employees while improving organizational performance by improving their quality of working life. The present study aimed to investigate the relationship between perceived organizational justice and quality of working life mediated by job involvement among the Iranian Red Crescent Society staff. Methods: This descriptive-correlational study employed structural equation modeling to investigate the relationship between variables. The statistical population consisted of all staff of the Red Crescent Society of Yazd Province in 2022-2023. In this study, 304 people were selected as participants through convenience sampling. The participants were asked to fill out the research measurement tools (i.e., quality of working life questionnaire, perceived organizational justice questionnaire, and job involvement scale). The proposed model was evaluated using structural equation modeling. The bootstrap test was used to test indirect relationships between the research variables. Results: The analysis of demographic data showed that the mean age of participants was 32.52±4.16 years. Moreover, 265 (87.17%) participants were male and 39 (12.83%) were female. The results demonstrated a significant relationship of perceived organizational justice with quality of working life and job involvement (P<0.001). A significant relationship also existed between job involvement and quality of working life among the Iranian Red Crescent Society staff (P=0.002). The results also demonstrated the significant relationship of perceived organizational justice with the quality of working life mediated by job involvement (P=0.014). Conclusions: Perceived organizational justice and job involvement had a positive, significant relationship with the quality of working life. Hence, organizational managers are advised to pay more attention to perceived organizational justice and job attachment.